2012
DOI: 10.1111/j.1524-4725.2011.02221.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus in the Treatment of Chronic and Refractory Late-Onset Immune-Mediated Adverse Effects Related to Silicone Injections

Abstract: Tacrolimus is an effective and well-tolerated drug in cases of severe and refractory late-onset inflammatory reactions, including large panniculitis, that complicate silicone gel injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Eight human studies (including 168 patients) have investigated the presence of bacteria on samples from LIRs after filler use [ 7 , 8 , 19 , 23 , 28 , 31 33 ]. Six studies were cross-sectional studies, while two studies were case series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight human studies (including 168 patients) have investigated the presence of bacteria on samples from LIRs after filler use [ 7 , 8 , 19 , 23 , 28 , 31 33 ]. Six studies were cross-sectional studies, while two studies were case series.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous human studies have shown the presence of bacteria in material derived from patients with LIRs (Table 7 in ESM) [7,8,23,28,31,32]. Two studies did not detect any bacteria in the collected samples [19,33]. The (mainly Staphylococcus epidermidis) and Propionibacterium acnes, which were detected in up to 98% of positive cultures, and which lead to the hypothesis that the presence of these bacteria is involved in development of LIRs [7,8,24,28,31,32].…”
Section: Discussion Bacterial Contamination and Lirsmentioning
confidence: 99%
“…The ability of silicone to initiate immunologic processes remains to be clarified. An exhaustive federally sponsored review failed to find evidence to support immunological effects [70]. …”
Section: Resultsmentioning
confidence: 99%
“…Studies published after the patient received treatment suggest tacrolimus may be beneficial in the treatment of chronic and refractory late-onset immune-mediated adverse effects secondary to silicone injections [11]. However, the small sample size of the study necessitates further validation of the results [12].…”
Section: Discussionmentioning
confidence: 96%